Pengaruh Edukasi 1000 Hari Pertama Kehidupan (HPK) Terhadap Pengetahuan Dan Sikap Wanita Usia Subur (WUS) - Hidayati, Diah Ulfa; Yulastini, Fitria; Fajriani, Evalina (Holistic Nursing and Health Science, 2022)
Introduction: Indonesia's health development still facing various challenges, one of which is the high incidence of stunting in children under five. Based on a preliminary study conducted in Perina Village, Jonggat District, Central Lombok Regency, mothers' knowledge and attitudes about caring for the first 1000 days of life (HPK) were still low. The low knowledge and attitude of mothers about nutrition in 1000 HPK can lead malnutrition conditions that occur since in the womb and early period after birth so it can affect growth and development problems in the future. The government has promoted the "1000 HPK Movement" as an effort to improve nutrition, but the problem of nutrition in society has not been optimally resolved. To support the government's program, it is necessary to conduct education as an effort to increase mothers' knowledge and attitudes about 1000 HPK.Methods: This research is a pre-experimental study with one group pretest-posttest design. This research was conducted in Perina Village, Jonggat District, Central Lombok Regency in August 2022. The population in this study were all women of childbearing age (WUS) who live in Perina Village. The sample in this study were 30 respondents who were taken by purposive sampling technique with predetermined inclusion and exclusion criteria. The independent variable in this study was the education of 1000 HPK and the dependent variable was the knowledge and attitudes of WUS. The 1000 HPK education was carried out using the discourse method with leaflets as media. Pretest and posttest with questionnaires were given before and after education to measure the level of knowledge and attitudes of WUS about 1000 HPK. Data analysis used the Wilcoxon test in the SPSS 23 program.Results: There are differences in WUS knowledge and attitudes before and after treatment. From the results of the Wilcoxon test, the value of p = 0.000 was obtained for the knowledge variable and p = 0.001 for the attitude variable.Conclusion: There is an effect of education on WUS knowledge and attitudes about 1000 HPK. Education about 1000 HPK must be carried out regularly with a variety media to increase people's knowledge and attitudes as an effort to prevent stunting and other nutritional problems.Keywords: 1000 HPK, Education, Women of Childbearing Age (WUS).